Experimental Study of Impact of Foul Release with Low Surface Energy on Ship Resistance - Kianejad SS; Seif MS; Ansarifard N (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2015)
A comparison between coating frictional resistances of several ship hulls has been conducted by experimental studies (Foul Release and conventional paint) in the unfouled conditions in Hydrodynamic open water tests in a lake using a ship model test. Models are completely similar, in order to eliminate other factors of resistance such as wave making resistance and viscous pressure resistance. Foul Release systems based on silicon offer a low surface energy and smooth surface that prevents adhesion of fouling organisms on underwater hulls. Wall roughness measurement was carried out by roughness analyzer and there is not much difference between Foul Release and conventional paint roughness. The results indicate that model with low surface energy has lower resistance compared to model with higher energy surface.